Relative decrease of tracer gas concentration as a measure of the ventilation effectiveness - Muhič, Simon (Strojniški vestnik, 2008)
An analysis of the ventilation effectiveness measured on a prototype system for local air-conditioning named PERMICS (Personal Microclimate System) was made based on simultaneous measurements of velocity field and of tracer gas concentration using the decay method. A new parameter based on a relative decrease of tracer gas concentration in the first minute of system operation dC(1) was introduced. The newly defined parameter has been verified by simulation results from commercial computational fluid dynamics (CFD) software. The usefulness of the parameter is the possibility to make quick measurements of the local efficiency of personalized ventilation systems.
Keywords: zrak; klimatizacija; prezračevanje; učinkovitost; efficiency